Mycobacterial Trehalose 6,6′-Dimycolate–Induced M1-Type Inflammation - Nguyen, Thao K.T. (Am J Pathol, 2020)
Murine models of Mycobacterium tuberculosis (Mtb) infection demonstrate progression of M1-like (proinflammatory) and M2-like (anti-inflammatory) macrophage morphology following primary granuloma formation. The Mtb cell wall cording factor, trehalose 6,6′-dimycolate (TDM), is a physiologically relevant and useful molecule for modeling early macrophage-mediated events during establishment of the tuberculosis-induced granuloma pathogenesis. Here, it is shown that TDM is a major driver of the early M1-like macrophage response as seen during initiation of the granulomas of primary pathology. Proinflammatory cytokines tumor necrosis factor-α, IL-1β, IL-6, and IL-12p40 are produced in lung tissue after administration of TDM to mice. Furthermore, CD11b(+)CD45(+) macrophages with a high surface expression of the M1-like markers CD38 and CD86 were found present in regions of pathology in lungs of mice at 7 days post-TDM introduction. Conversely, only low phenotypic marker expression of M2-like markers CD206 and EGR-2 were present on macrophages. These findings suggest that TDM plays a role in establishment of the M1-like shift in the microenvironment during primary tuberculosis.